2022
DOI: 10.1007/s13311-022-01280-1
|View full text |Cite
|
Sign up to set email alerts
|

Pridopidine Promotes Synaptogenesis and Reduces Spatial Memory Deficits in the Alzheimer's Disease APP/PS1 Mouse Model

Abstract: Sigma-1 receptor agonists have recently gained a great deal of interest due to their anti-amnesic, neuroprotective, and neurorestorative properties. Compounds such as PRE-084 or pridopidine (ACR16) are being studied as a potential treatment against cognitive decline associated with neurodegenerative disease, also to include Alzheimer’s disease. Here, we performed in vitro experiments using primary neuronal cell cultures from rats to evaluate the abilities of ACR16 and PRE-084 to induce new synapses and spines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Acupuncture can reduce oxidative stress and reduce neuroinflammation through multiple signal transduction pathways, Aβ Production, aggregation, and phosphorylation of Tau. Beura et al, 2022;Estévez-Silva et al, 2022;Maina et al, 2022). We believe that abnormal mitochondria in susceptible neurons play a source role by providing diffusible hydrogen peroxide on the membrane to the surrounding cytoplasm, as shown in Figure 3.…”
Section: Acupuncture Ameliorates Neuronal Antioxidant Damage As Well ...mentioning
confidence: 95%
“…Acupuncture can reduce oxidative stress and reduce neuroinflammation through multiple signal transduction pathways, Aβ Production, aggregation, and phosphorylation of Tau. Beura et al, 2022;Estévez-Silva et al, 2022;Maina et al, 2022). We believe that abnormal mitochondria in susceptible neurons play a source role by providing diffusible hydrogen peroxide on the membrane to the surrounding cytoplasm, as shown in Figure 3.…”
Section: Acupuncture Ameliorates Neuronal Antioxidant Damage As Well ...mentioning
confidence: 95%
“…Furthermore, the density of hyper-reactive astrocytes was reduced by the administration of PRE-084 [ 391 ], suggesting PRE-084 may play an anti-inflammatory role. PRE-084 could also increase mushroom dendritic spine formation in the hippocampus of transgenic rats expressing presenilin-1 (PS1) and human APP (Swe) [ 393 ].…”
Section: Sigma Receptor Ligands For Neurological Diseasementioning
confidence: 99%
“…Pridopidine protects against NMDA-induced oxidative stress in primary hippocampal cultures and can increase mushroom dendritic spine formation in the hippocampus of transgenic rats expressing presenilin-1 (PS1) and human APP (Swe) , as well as reduce deficits in spatial learning [ 393 ]. The study also showed that pridopidine induced ERK and AKT phosphorylation.…”
Section: Sigma Receptor Ligands For Neurological Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Spatial learning and memory impairment are common behavioral indicators used to assess the neurodegeneration status in mice. In our previous study, we performed the Morris water maze (MWM) test and active avoidance test to assess the effect of ergothioneine on the spatial learning and memory function in the C57BL/6JNarl mice . However, the effect of parapyruvate on inducing behavioral changes in the MWM and active avoidance tests is unknown.…”
Section: Introductionmentioning
confidence: 99%